Transcriptome and metabolome analyses reveal the key genes related to grain size of big grain mutant in Tartary Buckwheat (Fagopyrum tartaricum) - Fang, Xiaomei; Wang, Yingqian; Cui, Jingbin; Yue, Linqing; Jiang, Aohua; Liu, Jiaqi; Wu, Yichao; He, Xingxing; Li, Chunhua; Zhang, Jian; Ding, Mengqi; Yi, Zelin (Frontiers in Plant Science, 2022)
Grain size with high heritability and stability is an important selection target during Tartary buckwheat breeding. However, the mechanisms that regulate Tartary buckwheat grain development are unknown. We generated transcriptome and metabolome sequencing from 10 and 15 days past anthesis (DPA) grains of big grain mutant (bg1) and WT, and identified 4108 differentially expressed genes (DEGs) including 93 significantly up-regulated differential genes and 85 significantly down-regulated genes in both stages, simultaneously. Meanwhile, we identified DEGs involved in ubiquitin-proteasome pathway, HAI-KU (IKU) pathway, mitogen-activated protein kinase (MAPK) signaling pathway, plant hormone (auxin, brassinosteroids and cytokinins) transduction pathway and five transcription factor families, including APETALA (AP2), GROWTH-REGULATING FACTORS (GRF), AUXIN RESPONSE FACTOR (ARF), WRKY and MYB. Weighted gene co-expression network analysis (WGCNA) was performed and obtained 9 core DEGs. Conjoint analyses of transcriptome and metabolome sequencing screened out 394 DEGs. Using a combined comprehensive analysis, we identified 24 potential candidate genes that encode E3 ubiquitin-protein ligase HIP1, EMBRYO-DEFECTIVE (EMB) protein, receptor-like protein kinase FERONIA (FER), kinesin-4 protein SRG1, and so on, which may be associated with the big-grain mutant bg1. Finally, a quantitative real-time Polymerase Chain Reaction (qRT-PCR) assay was conducted to validate the identified DEGs. Our results provide additional knowledge for identification and functions of causal candidate genes responsible for the variation in grain size and will be an invaluable resource for the genetic dissection of Tartary buckwheat high-yield molecular breeding.